1986
DOI: 10.1007/bf00172881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dihydroergosine (DHESN) on the serotoninergic system and behaviour: Is DHESN a new antidepressive agent?

Abstract: Acute (50.0 mg/kg) and repeated (0.1-10.0 mg/kg) administration of dihydroergosine (DHESN) to rats over 5 days lowered the concentration of 5-HIAA in the brain. DHESN given acutely increased the brain 5-HT in p-CPA-treated animals and diminished the probenecid-induced increase in brain 5-HIAA. In pargyline-treated rats DHESN enhanced the 5-HT/5-HIAA ratio. DHESN administered to rats repeatedly over 5 days decreased the level of 5-HT in blood platelets, and in vitro at concentrations of 10(-4) M and 10(-3) M in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Thus, we have shown that dihydroergosine stimulates the 5-HT syndrome in rats Manev, 1987, 1988;Peri~i6 and Muck-Seler, 1990), inhibits the head-twitch behavior in rats and mice (Peri~i6 and Manev, 1988;Peri~i6 and Muck-Seler, 1990), possesses antiaggressive properties in two models of isolation induced aggressiveness (Manev et al, 1989), and produces a shortening of immobility in the forced swimm test (Manev and Peri~i6, 1988). Biochemical changes observed in the rat brain after administration of dihydroergosine also indicate the involvement of the 5-HT system (Peri~i6 et al, 1986). Recently, on the base of the behavioral studies we have suggested that both the classic antidepressant imipramine, and a possible antidepressant dihydroergosine-possess two components-one stimulating the 5-HT syndrome in rats, presumably by a 5-HT1 A-mediated mechanism, and the other inhibiting 5-HT 2 binding sites (Peri~i6 and Muck-Seler, 1990).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, we have shown that dihydroergosine stimulates the 5-HT syndrome in rats Manev, 1987, 1988;Peri~i6 and Muck-Seler, 1990), inhibits the head-twitch behavior in rats and mice (Peri~i6 and Manev, 1988;Peri~i6 and Muck-Seler, 1990), possesses antiaggressive properties in two models of isolation induced aggressiveness (Manev et al, 1989), and produces a shortening of immobility in the forced swimm test (Manev and Peri~i6, 1988). Biochemical changes observed in the rat brain after administration of dihydroergosine also indicate the involvement of the 5-HT system (Peri~i6 et al, 1986). Recently, on the base of the behavioral studies we have suggested that both the classic antidepressant imipramine, and a possible antidepressant dihydroergosine-possess two components-one stimulating the 5-HT syndrome in rats, presumably by a 5-HT1 A-mediated mechanism, and the other inhibiting 5-HT 2 binding sites (Peri~i6 and Muck-Seler, 1990).…”
Section: Introductionmentioning
confidence: 84%
“…Studies conducted in our laboratory have revealed that the ergot alkaloid dihydroergosine affects central serotoninergic transmission. On the basis of biochemical and behavioural experiments we have suggested that this drug might be a new antidepressant (Peri~i6 et al, 1986;Peri~i6 and Manev, 1987;Manev and Peri~i6, 1988). Thus, we have shown that dihydroergosine stimulates the 5-HT syndrome in rats Manev, 1987, 1988;Peri~i6 and Muck-Seler, 1990), inhibits the head-twitch behavior in rats and mice (Peri~i6 and Manev, 1988;Peri~i6 and Muck-Seler, 1990), possesses antiaggressive properties in two models of isolation induced aggressiveness (Manev et al, 1989), and produces a shortening of immobility in the forced swimm test (Manev and Peri~i6, 1988).…”
Section: Introductionmentioning
confidence: 97%
“…Dihydroergosine has been shown to decrease the turnover of serotonin (5-HT) in the whole brain (Peri6i6 et al, 1986b), to potentiate long-lastingly the 5-HT syndrome in the rat Manev, 1987, 1988) and to inhibit the headtwitch response in rats and mice . Recently, some neuropharmacological properties of this substance have been discovered.…”
Section: Introductionmentioning
confidence: 99%